Factors influencing adoption of dairy technology on small holder dairy farmers in selected zones of Amhara and Oromia National Regional States, Ethiopia - Dehinenet, G.; Mekonnen, H.; Kidoido, Michael M.; Ashenafi, M.; GuerneBleich, E. (2014)
The dairy technology in Ethiopia was promoted and disseminated through both Non-Governmental and Governmental Organization with the aim of improving output, increasing incomes and consequently improving the livelihoods of the small holder farmers. This paper used the Heckman two-stage model to identify the factors that influence adoption of the technology and level of adoption. Farm and household level data were obtained from 384 farmers consisting of 192 adopters and 192 non-adopters. The results demonstrated that family size, farming experience, availability of dairy production extension services, availability of cross breed cows, accessibility of saving institutions, total income from milk and milk products, availability of training on livestock, age of household head and off-farm activity participation played significant roles on both the probability of dairy technology adoption and its level of adoption.